Prophetic Communication: Islam as Knowledge Practice - Muhammad Najmuddin; Muhammad Amri; Andi Aderus (State Islamic Institute of Bone, Indonesia, 2022)
Prophetic Communication is briefly defined as 'Prophetic Communication' or 'Apostolic Communication'. Prophetic communication does not only mean